Corporate Social Responsibility (CSR) Practices in Small and Medium Enterprises (SMEs) in Sub-Saharan Africa : An Applied Reading in Gabon - (:unkn) unknown (My University, 2023)
Corporate Social Responsibility (CSR) is a concept that has spread to all continents from a Western perspective. However, the Western approach to CSR raises the question of its adequacy in other contexts. Indeed, the use of CSR theories and models developed in the Western context in Africa is increasingly being called into question. This means that the researcher must use adapted theoretical frameworks and deploy innovative research devices so that the results produced are not decontextualized, but are culturally and historically rooted in a territory. However, the literature on CSR practices in African SMEs shows an absence of traditional CSR practices to the detriment of Western practices. This thesis highlights CSR practices that reflect the empirical reality of Gabonese SMEs.Two main findings emerged from this research. Firstly, informal Western practices in three dimensions : social, societal and environmental. Secondly, underlying cultural and traditional practices, in the form of tontine solidaire, interdependent relationships, social habits and the sacredness of the word. It is by taking African values into account that CSR practices are effectively integrated into SMEs. Moreover, these results are consistent with African management styles described as hybrid, because corporate governance very often oscillates between tradition and modernity.
Keywords: African Research